Fine motor skills assessment instruments for preschool children with typical development: a scoping review - Zhang, Bai-Fa; Lin, Zhi-Cheng; Li, Chao (Frontiers in Psychology, 2025)
PurposeThis study aims to systematically evaluate the available scientific knowledge on fine motor skills assessment instruments for typically developing preschool children.MethodsRelevant literature was systematically retrieved from Web of Science Core Collection, PubMed, Medline, CNKI, and Wanfang databases from their inception to June 9, 2023. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR), included literature was compiled and analyzed.ResultsIn total, 58 studies reporting 14 instruments met inclusion criteria: performance-based tests (n = 11), informant-based questionnaires (n = 2), and one computer-assisted tool. Based on different types and development purposes, the measurement dimensions and items had varying emphases, and there is no recognized gold standard yet. The reliability of measurements was generally good, while validity needs improvement.ConclusionGiven the distinct strengths and limitations of available FMS assessment tools, we suggest that selection should align with specific objectives: the ASQ may be most suitable for large-scale screening, the MABC for general FMS assessment in small groups, the Beery VMI for visual-motor integration, and the TIHM for fine motor control assessment.